Analisis Kualitas Pelayanan Pada Unit Perijinan Angkutan Dan Kendaraan Wajib Uji Dinas Perhubungan Kabupaten Karanganyar - Fachry Prasetyo; Priyanto Susiloadi (JURNAL ILMIAH EDUNOMIKA, 2020)
Good service quality in public services will give an impetus to the user community to give a good assessment. Good service by the State Civil Servants (ASN) in the Transportation Obligatory Licensing Unit (UPAKWU) in the Karanganyar District Transportation Department was apparently still receiving complaints from the service user community. This shows that there are still some shortcomings in the implementation of the service system in the office. The sampling technique uses accidental sampling method. The data used are primary data obtained directly from respondents by providing a list of questions or questionnaires. Data analysis techniques using Importance-Performance Analysis (IPA) are used to measure the level of satisfaction of someone over the performance of other parties, and Cartesian Diagrams to determine service indicators that satisfy or do not satisfy consumers. The results showed that: Service quality in UPAKWU Karanganyar Regency according to customer perceptions has not been satisfactory, despite having good service performance / above average. This is based on the results of the Importance Performance Analysis analysis which gets a result of 94.36% (Total Tki